2016
DOI: 10.1016/j.chemosphere.2016.08.023
|View full text |Cite
|
Sign up to set email alerts
|

Maternal and fetal exposure to cadmium, lead, manganese and mercury: The MIREC study

Abstract: Given the susceptibility of the fetus to toxicants, it is important to estimate their exposure. Approximately 2000 pregnant women were recruited in 2008-2011 from 10 cities across Canada. Cd, Pb, Mn and total Hg were measured in maternal blood from the 1st and 3rd trimesters, umbilical cord blood, and infant meconium. Nutrient intakes of vitamin D, iron, and calcium (Ca) were assessed using a food frequency questionnaire and a dietary supplement questionnaire. Median concentrations in 1st trimester maternal bl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

18
68
6
6

Year Published

2017
2017
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 168 publications
(98 citation statements)
references
References 74 publications
18
68
6
6
Order By: Relevance
“…Our data however contrast with in vitro evidence that show >50% lower Cd levels with Zn and Mn treatment, and negative relationships between Zn, Cu and Mg with Cd [62]. These data provide early evidence that some essential metals, including Mn [63] may not mitigate exposure and effects of these metals. Specific mineral combinations that mitigate exposure may depend on the underlying nutritional status and may therefore vary by population exposed to Pb or Cd.…”
Section: Discussioncontrasting
confidence: 99%
“…Our data however contrast with in vitro evidence that show >50% lower Cd levels with Zn and Mn treatment, and negative relationships between Zn, Cu and Mg with Cd [62]. These data provide early evidence that some essential metals, including Mn [63] may not mitigate exposure and effects of these metals. Specific mineral combinations that mitigate exposure may depend on the underlying nutritional status and may therefore vary by population exposed to Pb or Cd.…”
Section: Discussioncontrasting
confidence: 99%
“…For the general population, the most common sources of exposure for these heavy metals are via contaminated air and food, although exposure to tobacco smoke is also a significant source of exposure for cadmium and lead 116,117. Although lead levels have been continuously decreasing in North America,118 a recent study found that >99% of women had detectable blood lead levels during pregnancy 119. Similarly, the majority of pregnant women had detectable blood levels of cadmium (>95%) and mercury (>85%) 119.…”
Section: Metalsmentioning
confidence: 99%
“…Although lead levels have been continuously decreasing in North America,118 a recent study found that >99% of women had detectable blood lead levels during pregnancy 119. Similarly, the majority of pregnant women had detectable blood levels of cadmium (>95%) and mercury (>85%) 119. Given the widespread exposure to cadmium, mercury, and lead, there have been a number of studies investigating the relationship between maternal body burden of these metals and adverse pregnancy outcomes (eg, spontaneous abortion, stillbirth, preterm labor, and low birth weight).…”
Section: Metalsmentioning
confidence: 99%
“…Therefore, the placenta provides a partial barrier against this metal [20]. As a result, Cd levels in cord blood are typically lower than maternal Cd levels [40]. Nevertheless, in utero Cd exposure has been linked to a range of adverse health effects, including impaired growth and neurodevelopment [41][42][43].…”
Section: Cadmiummentioning
confidence: 99%